2011
DOI: 10.4103/2230-8210.85579
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and psychiatric disorders

Abstract: Interface of diabetes and psychiatry has fascinated both endocrinologists and mental health professionals for years. Diabetes and psychiatric disorders share a bidirectional association -- both influencing each other in multiple ways. The current article addresses different aspects of this interface. The interaction of diabetes and psychiatric disorders has been discussed with regard to aetio-pathogenesis, clinical presentation, and management. In spite of a multifaceted interaction between the two the issue r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
119
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 63 publications
4
119
0
2
Order By: Relevance
“…Studies by Islam et al [29] and Saadalla et al [30] independently showed that depression and T2DM are significantly associated. The finding of our study regarding the association of anxiety is also supported by studies conducted by Balhara [8] (P = 0.02), Engum, [7] Almawi et al [31] (P < 0.001), and Afzal et al [32] (OR = 5.348;CI = 2.15-13.29). Stress is also studied as an independent risk factor by various authors like Dutt et al [33] (OR = 4.3;Cl = 2-9.4; P < 0.001), Majgi et al [34] (OR = 10.5; CI = 1.3-90.7, P = 0.03), and Afzal et al [32] (OR = 4.52; CI = 1.95-10.50) and emerged as an independent risk factor for T2DM, which is in concordance with our study.…”
Section: Discussionsupporting
confidence: 79%
“…Studies by Islam et al [29] and Saadalla et al [30] independently showed that depression and T2DM are significantly associated. The finding of our study regarding the association of anxiety is also supported by studies conducted by Balhara [8] (P = 0.02), Engum, [7] Almawi et al [31] (P < 0.001), and Afzal et al [32] (OR = 5.348;CI = 2.15-13.29). Stress is also studied as an independent risk factor by various authors like Dutt et al [33] (OR = 4.3;Cl = 2-9.4; P < 0.001), Majgi et al [34] (OR = 10.5; CI = 1.3-90.7, P = 0.03), and Afzal et al [32] (OR = 4.52; CI = 1.95-10.50) and emerged as an independent risk factor for T2DM, which is in concordance with our study.…”
Section: Discussionsupporting
confidence: 79%
“…Our study showed stroke was the most common cause of delirium (31%) followed by hyponatraemia (16%). In our study out of 100 patients, 37 were suffering from diabetes mellitus and amongst them most common cause of the delirium was hypoglycaemia (29%) followed by nonhaemorrhagic stroke (18.9%), same as study by Yatin Pal Singh Balhara et al 9 In our study, hyponatraemia was the second commonest cause (16%) and the affected age group was 66 -70 yrs. (37.5%).…”
Section: Discussionsupporting
confidence: 69%
“…This disease is associated with a broad spectrum of complications such as neuropathy, retinopathy, nephropathy, and atherosclerosis [2] . In addition, psychiatric comorbidities such as dementia, depression, and anxiety are experienced by the majority of diabetic patients [3] , resulting in a reduction of quality of life, poor treatment outcomes, and increase in the cost burden of medical care [4] .…”
Section: Introductionmentioning
confidence: 99%